2007
DOI: 10.1111/j.1365-2958.2007.05726.x
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of zinc homeostasis by the ZafA transcriptional activator is essential for Aspergillus fumigatus virulence

Abstract: SummaryWe have previously shown that Aspergillus fumigatus is able to grow in zinc-limiting media and that this ability is regulated at transcriptional level by both the availability of zinc and pH. When A. fumigatus grows as a pathogen, it must necessarily obtain zinc from the zinc-limiting environment provided by host tissue. Accordingly, the regulation of zinc homeostasis by some zinc-responsive transcriptional regulator in A. fumigatus must be essential for fungal growth within tissues of an immunocompromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
133
0
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(156 citation statements)
references
References 43 publications
4
133
0
15
Order By: Relevance
“…In the za P region, there are three 15-bp consensus sequences with a common 5Ј-CAAGGT-3Ј core. These 15-bp sequences were designated ZR1 to ZR3 (for zinc response), since preliminary data obtained at our laboratory have indicated that they are cis-acting sequences required for regulating the expression of zrfC and aspf2 at the transcriptional level (unpublished data), most likely through binding of the zincresponsive transcriptional activator ZafA (28). In addition, in the za P region there are six PacC-like binding motifs (5Ј-GCC ARG-3Ј) (42) designated PR1 to PR6 (for pH response).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the za P region, there are three 15-bp consensus sequences with a common 5Ј-CAAGGT-3Ј core. These 15-bp sequences were designated ZR1 to ZR3 (for zinc response), since preliminary data obtained at our laboratory have indicated that they are cis-acting sequences required for regulating the expression of zrfC and aspf2 at the transcriptional level (unpublished data), most likely through binding of the zincresponsive transcriptional activator ZafA (28). In addition, in the za P region there are six PacC-like binding motifs (5Ј-GCC ARG-3Ј) (42) designated PR1 to PR6 (for pH response).…”
Section: Resultsmentioning
confidence: 99%
“…Expression of both zrfC and aspf2 is induced in zinc-limiting media by the ZafA zinc-responsive transcriptional activator. The ZafA protein of A. fumigatus activates the transcription of the zrfA and zrfB genes under acidic zinc-limiting conditions (28). Therefore, it would be expected that the transcription of these genes as well as of others related to zinc homeostasis in A. fumigatus would also be regulated by ZafA under alkaline zinc-limiting conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A. fumigatus uses siderophores for both iron acquisition and intracellular iron storage [51], and disrupting the siderophore biosynthetic pathway at multiple steps has revealed that A. fumigatus relies heavily on these low-molecular weight chelators for growth in the iron-limited environment of the host [51][52][53]. Zinc also has limited bioavailability in vivo, and the zincresponsive transcriptional activator ZafA is required to support virulence, presumably by enhancing zinc uptake mechanisms [54].…”
Section: Meeting Nutritional Requirementsmentioning
confidence: 99%